All the glimmering stars : a novel - Sullivan, Mark T. (Seattle : Lake Union Publishing, 2024)
Two 1990s Ugandan teens are kidnapped and forced into the Lord's Resistance Army where they dream of surviving their captivity and their intent to remain good people.
Keywords: Kony, Joseph -- Fiction; Opoka, Anthony -- Fiction; Okori, Florence -- Fiction; Lord's Resistance Army. -- Fiction; Child soldiers -- Uganda -- Fiction; Uganda -- History -- 1979- -- Fiction; Historical fiction; Biographical fiction; Novels